Remarks on the life and research of Roland L. Dobrushin. (1996) - Minlos, R. A.; Pechersky, E. A.; Suhov, Yu. M.
Abstract : The life and research work of Professor R.L. Dobrushin (1929-1995) had a profound influence on several areas of probability theory, information theory, and mathematical physics. The paper contains a biographical note, a review of Dobrushin's results, and a list of his publications.